OP68 How is overweight/obesity across the life course associated with levels of adipokines, inflammatory and endothelial markers at age 60–64 years? Findings from the 1946 birth cohort. (2nd September 2014) - Murray, ET; Hardy, R; Hughes, A; Wills, AK; Sattar, N; Deanfield, J; Kuh, D; Whincup, P
Abstract : Background: There is growing evidence that early development of obesity influences cardiovascular risk later in life, but less is known about whether there are persistent effects of long-term excess body weight on biological markers associated with atherosclerosis, including adipokines, inflammatory and endothelial markers. Methods: Data from 1784 participants in the MRC National Survey of Health and Development were used to examine associations between overweight status at different ages (2, 4, 6, 7, 11, 15, 20, 26, 36, 43, 53 and 60–64 years) and measurements of adipokines (leptin, adiponectin), inflammatory markers (C reactive protein [CRP], Interleukin-6 [IL-6] and endothelial markers (E-selectin, Tissue plasminogen activator [t-PA] and von Willebrand factor [vWF]) at age 60–64 years. Additionally, model fit of different life course models (sensitive periods/accumulation) were compared using partial F-tests. Results: Overweight showed consistent positive associations with leptin, CRP, IL-6, E-selectin and t-PA and inverse associations with adiponectin; vWF was not consistently related across age. In age and sex-adjusted models fitted separately for each age, being overweight at 11 years and onwards was associated with adverse levels of adipokines and inflammatory markers and being overweight from 15 and onwards for endothelial markers. For CRP and adiponectin, an earlier association with overweight at 2 years was also apparent. Adjustment for overweight at age 60–64 years reduced all overweight associations at earlier ages, entirely explaining those for E-selectin and t-PA, but only partly explaining those for leptin, adiponectin, CRP and IL-6. An accumulation model best described the associations between overweight across the life course with adiponectin (mean percentage difference [95% CI] for each additional time overweight at age 15, 36 and 60–64: -12.8% [-16.3%, -9.1%], leptin: 60.2% [53.6%, 67.1%], CRP: 22.2% [15.7%, 29.0%] and IL-6: 15.6% [10.7, 20.7%]). For the endothelial markers, the accumulation model also explained the data as well as the saturated model, but the middle age sensitive period model provided a slightly better fit (mean percentage difference for overweight versus not overweight: E-selectin 17.0% [11.0%, 23.3%], t-PA 35.8% [26.6%, 45.6%]). Conclusion: The longer participants were overweight from adolescence to retirement age, the more adverse their levels of adipokines and inflammatory markers at 60–64 years, with overweight at 60–64 particularly important for endothelial markers. Given that children alive today are likely to spend more of their lives as overweight or obese than cohort members in this study, preventing the development of overweight before retirement age could have an appreciable benefit for prevention of cardiovascular diseases.